Her2 challenge contest: a detailed assessment of automated her2 scoring algorithms in whole slide images of breast cancer tissues - Qaiser, Talha; Mukherjee, Abhik; Reddy Pb, Chaitanya; Munugoti, Sai Dileep; Tallam, Vamsi; Pitkäaho, Tomi; Lehtimäki, Taina; Naughton, Thomas; Berseth, Matt; Pedraza, Aníbal; Mukundan, Ramakrishnan; Smith, Matthew; et al. (Wiley, 2018)
Aims